Colonic immune cells in irritable bowel syndrome: A systematic review and meta‐analysis. Issue 1 (29th August 2017) - Bashashati, M.; Moossavi, S.; Cremon, C.; Barbaro, M. R.; Moraveji, S.; Talmon, G.; Rezaei, N.; Hughes, P. A.; Bian, Z. X.; Choi, C. H.; Lee, O. Y.; Coëffier, M.; et al.
Abstract: Background & Aims: Increases in mucosal immune cells have frequently been observed in irritable bowel syndrome (IBS) patients. However, this finding is not completely consistent between studies, possibly due to a combination of methodological variability, population differences and small sample sizes. We performed a meta‐analysis of case– control studies that compared immune cell counts in colonic biopsies of IBS patients and controls. Methods: PubMed and Embase were searched in February 2017. Results were pooled using standardized mean difference (SMD) and were considered significant when zero was not within the 95% confidence interval (CI). Heterogeneity was assessed based on I 2 statistics where I 2  ≤ 50% and I 2  > 50% indicated fixed and random effect models, respectively. Key Results: Twenty‐two studies on 706 IBS patients and 401 controls were included. Mast cells were increased in the rectosigmoid (SMD: 0.38 [95% CI: 0.06‐0.71]; P  = .02) and descending colon (SMD: 1.69 [95% CI: 0.65‐2.73]; P  = .001) of IBS patients. Increased mast cells were observed in both constipation (IBS‐C) and diarrhea predominant IBS (IBS‐D). CD3 + T cells were increased in the rectosigmoid (SMD: 0.53 [95% CI: 0.21‐0.85]; P  = .001) and the descending colon of the IBS patients (SMD: 0.79, 95% CI [0.28‐1.30]; P  = .002). This was possibly in relation to higher CD4 + T cells in IBS (SMD: 0.33 [95% CI: 0.01‐0.65]; P  = .04) as there were no differences in CD8 + T cells. Conclusions & Inferences: Mast cells and CD3 + T cells are increased in colonic biopsies of patients with IBS vs non‐inflamed controls. These changes are segmental and sometimes IBS‐subtype dependent. The diagnostic value of the quantification of colonic mucosal cells in IBS requires further investigation. Abstract : Studies have indicated changes in the intestinal immune cell counts of IBS patients; however, these findings are not consistent. The current study shows that the number of colonic mast cells, CD3 + T cells and CD4 + T cells are increased in IBS. These changes are colonic segmental and sometimes IBS‐subtype dependent. Figure shows density/number of mast cells in colorectal biopsies of patients with IBS vs healthy controls. (A) Ascending colon, (B) Descending colon, (C) Rectosigmoid.